Melhor em casa: o desafio de cuidar - Andreia Devislanne Ribeiro (2020)
Population aging, that is, the increase in the relative weight of older people in the total population, was one of the major demographic events of the twentieth century and will certainly be maintained in the 21st century. The increase in the elderly in the population, associated with the growth of longevity, pose challenges in relation to care policies aimed at the aging population, among them the Home Care Policy (AD). In AD, caregiver / team / individual / family relationships are fundamental in the implementation of home care and improvement of the individual, reaffirming the importance of light technologies. This study aimed to know the daily life of the informal caregivers of the elderly attended by the Home Hospitalization Program (PID) of the city of Betim - MG and to identify the challenges faced in the care of elderly people dependent on life-sustaining technologies. It is believed that this was a way to evaluate the municipality's Home Internment Program. After all, the user's opinion, represented here by the informal caregiver, provides elements to understand how the program works in practice, raising possible gaps and potentialities. This exploratory and descriptive study was conducted through a qualitative approach with semi-structured interviews. The interview data were recorded, transcribed and analyzed using the thematic content analysis technique. The results pointed gaps regarding the structuring of the health care network in Betim. Through the reports of the caregivers interviewed in the PID, it was possible to highlight relevant factors for the structuring of the AD, such as access, comprehensiveness, resoluteness, universality and the organization of services. It is emphasized the distance between the ordinance that regulates the AD and the reality regarding the flow of referrals, supplies of inputs, being evidenced through the interviews of the caregivers of the AD. Once the paths taken by caregivers in search of health care were identified, the need for interdependence and complementarity between the services that make up the health care network was identified in order to ensure comprehensive care. Aspects related to the challenges and opportunities inherent in network articulation were also observed, among which the following stand out: the difficulty of articulation with primary care; lack of responsibility for services and lack of knowledge of people about the provision of health network services; poor communication between services. Among the opportunities, reference and counter-reference practices were evidenced. Home care is considered an important space in the reorganization of health work and in the reorganization of health care. . It is emphasized that initiatives of involvement, articulation, interaction and integration with other health services are fundamental foundations to reach the assumptions of the health care network.